Manajemen Anestesi pada Seksio Sesaria dengan Hipotiroid - Kurniawaty, Juni; Adiyanto, Bowo; Joni, Rendy Pranda (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
Thyroid disease is a disorder that affects the thyroid gland. Thyroid hormones regulate metabolism and affect nearly every organ in the body. The management of anesthesia on the hypothyroid is crucial and consist of preoperative, intraoperative, and postoperative management. We reported a 36-year-old female patient with multigravida and hypothyroid on therapy, which would performed sectio caesarea. Patient had hypothyroid and consumed levothyroxine since a year earlier. Spinal regional anesthesia with low doses was administered and sedation was neither prescribed before nor during surgery to maintain hemodinamic stability. A pregnant women with hypothyroidism need special management of anesthesia. Hypothyroid patients are very sensitive to anesthetic drugs so that preoperative sedation should be avoided. During intraoperation, surveillance of haemodynamics must be strict because hypothyroidism can trigger refractory hypotension. Sedation drugs should not use both in preoperative and intraoperative period.